In-situ measurement of wall thermal performance : data interpretation and apparatus design recommendations - 286243 Modera, M. P.; Sherman, M. H.; De Vinuesa, S. G.; American Society for Testing Materials Symposium on Thermal Insulation Materials System (1984 : Dallas) (Berkeley, Calif. : University of California, 1984)
03